Desenvolvimento musical de crianças autistas em diferentes contextos de aprendizagem: um estudo exploratório - Gleisson do Carmo Oliveira (2015)
This work presents an exploratory research that aimed to study the musical development of two three year old children, diagnosed with mild autism in two different learning contexts and to identify the probable factors that influenced this process. Therefore, two children with autism had one semester of music lessons, each one in a different context: a special one, composed exclusively of autistic children; and a mixture one, composed of normal and autistic children. The classes were filmed and the musical development of children was analyzed by a musical educator, a music therapist and a music neuroscientist, all of them specialists in children this age. The data provided by the jury went through the content analysis technique. This analysis pointed patterns that led to categories which offered the basis for the evaluation of the development achieved by the two children in the music lessons. Partially structured interviews were conducted with parents, to a better understanding of the results. The results pointed to a significant musical / general development of both children in their learning contexts, demonstrating how beneficial music making can be, independent of the learning context, and showed that music, in fact, may affect human being as a whole. It was concluded that the learning environment suffers numerous influences, ranging from individuals present in the classroom, to the family habits and to individual characteristics of the Autism Spectrum Disorder. A contribution of this research was the possibility to develop a protocol to evaluate music/general development of children with mild autism, based on the categories pointed by the jury. This protocol should be developed and tested in further researches.